2023
DOI: 10.1021/acs.macromol.3c00317
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Investigation of the Pressure Dependence of Glass Formation in a Charged Polymer Melt

Abstract: Most commodity polymers are derived from petroleum raw materials, and correspondingly, these materials are normally uncharged and nonpolar, attributes that make this class of material relatively insoluble in water and relatively slow to breakdown in the environment. Natural and synthetic charged polymer materials often do not exhibit these drawbacks, thereby offering the potential for being more sustainable. As with all polymer materials, properties related to glass formation play a central role in the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…Packing frustration is quantified in the GET by the relative values of α P and S (0). , In particular, the GET predicts that the fragility of glass formation should be larger in polymeric glass-forming liquids having a higher α T or S (0). Notably, this general trend has been confirmed in simulations of polymer fluids having a wide range of fragility values, , as well as in measurements on metallic glass materials , and numerous other glass-forming materials . The importance of thermal expansion in understanding the fragility of glass formation has also been emphasized in the model of Zaccone and co-workers. ,, …”
Section: Resultsmentioning
confidence: 69%
“…Packing frustration is quantified in the GET by the relative values of α P and S (0). , In particular, the GET predicts that the fragility of glass formation should be larger in polymeric glass-forming liquids having a higher α T or S (0). Notably, this general trend has been confirmed in simulations of polymer fluids having a wide range of fragility values, , as well as in measurements on metallic glass materials , and numerous other glass-forming materials . The importance of thermal expansion in understanding the fragility of glass formation has also been emphasized in the model of Zaccone and co-workers. ,, …”
Section: Resultsmentioning
confidence: 69%
“…Incorporation of SiC and OI-POSS-coated SiC into the epoxy system resulted in improved flexural strength, shear modulus, and T g , compared to the neat epoxy resin . One of the important and rather general influences of adding polar or hydrogen-bonding additives as a cross-linking agent or charged or polar molecular species to a polymer material is the increase of the cohesive density energy of the material. Xia and co-workers have recently shown that increasing the strength of the cohesive interaction can lead to a significant increase in T g while at the same time leading to a significant decrease in the fragility of glass formation in the thermoset material.…”
Section: Introductionmentioning
confidence: 99%